2022
DOI: 10.1002/jbm.b.35194
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stromal cells are sensitive to discrete surface alterations in build and post‐build modifications of bioinspired Ti6Al4V 3D‐printed in vitro testing constructs

Abstract: Current standards in bone‐facing implant fabrication by metal 3D (M3D) printing require post‐manufacturing modifications to create distinct surface properties and create implant microenvironments that promote osseointegration. However, the biological consequences of build parameters and surface modifications are not well understood. This study evaluated the relative contributions of build parameters and post‐manufacturing modification techniques to cell responses that impact osseointegration in vivo. Biomimeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Average areal surface roughness and peak‐to‐valley height were calculated using the Zeiss topography module. Skewness and kurtosis were assessed as described previously 29 …”
Section: Methodsmentioning
confidence: 99%
“…Average areal surface roughness and peak‐to‐valley height were calculated using the Zeiss topography module. Skewness and kurtosis were assessed as described previously 29 …”
Section: Methodsmentioning
confidence: 99%
“…In vitro results demonstrated that the adhesion, proliferation, and osteogenic differentiation of rat BMSCs were significantly enhanced on the modified Ti alloy scaffolds, ameliorating the cytocompatibility and osseointegration of the porous Ti alloy implants. Additionally, Berger et al [142] compared sandblasting and acid etching (GB+AE) with GB+AE followed by hot isostatic pressing (HIP) (GB+AE, HIP) by culturing human bone marrow matrix cells (MSCs) for seven days to determine the cell response. The results showed that all exhibited the ability to differentiate MSCs into osteoblasts, with the optimal response of MSCs to the micro/nanostructures produced by the final GB+AE HIP treatment.…”
Section: Functional Composite Coatingsmentioning
confidence: 99%